The relationship between environmental factors and opportunities to become entrepreneur among visually impaired in Terengganu / Zalinawati Abdullah, Nazlin Emieza Ngah and Rusnah Ismail - Abdullah, Zalinawati; Ngah, Nazlin Emieza; Ismail, Rusnah (2011)
An entrepreneur is individual that can be self-employed and offered the employment to others. This career is not only for normal people but it also appropriate for disable people such as visually impaired (VI) people. In order to form entrepreneur among VI people there are few factors should be considered. The scope of the study was emphasized the significant relationship between environmental factors (social factors, training and marketing network) among VI people that will grasp opportunities to become entrepreneurs. This study focused environmental factors (social factor, training and marketing network) as independent variables and the opportunities to become entrepreneur as dependent variable. The research is focusing on VI people that were registered with PERTIS (Persatuan Orang-Orang Cacat Penglihatan Islam Malaysia, Terengganu Province). This study used the quota sampling and emphasized only 50 ordinary members due to the time constraint and the disability of respondents. Using personally administered questionnaire with two types of Malay questionnaires which are common format and Braille format. The study found the environmental factors (social factors, training and marketing network) have marginal significant relationship with the opportunities to become entrepreneur. Based on the analysis, it indicated that the social factors are the main contribution to the entrepreneur’s opportunities.